Risk Factors Associated with Sick Building Syndrome Among Workers in High-Rise Office Buildings - Widya Ayu Oktavia; Onny Setiani; Tri Joko; Sulistiyani Sulistiyani; Suhartono Suhartono (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Indoor air quality is one of the crucial aspects of the work environment. Poor workplace conditions not only reduce comfort and job satisfaction but also significantly affect work productivity. One clinical manifestation of poor office environmental quality is the emergence of Sick Building Syndrome (SBS). The etiology of SBS is multifactorial, involving complex interactions between physical environmental factors (temperature, humidity, particulate dust), chemical factors (VOCs, CO₂), and biological agents, as well as individual characteristics and psychosocial conditions. This study aimed to determine the risk factors associated with the occurrence of SBS among employees of the Central Java Provincial Archives and Library Office. This research employed an analytical observational approach with a cross-sectional design involving 93 employees as respondents. The results showed that the average indoor air quality measurements in the work areas were as follows: humidity 56.30%, temperature 27.85oC, lighting intensity 170.04 lux, and air change per hour 3.43 times/hour. The prevalence of SBS among employees was 58.1%. There was not a significant association between temperature (p=0.035; RP=1.840), humidity (p=0.085; RP=0.712), lighting (p=0.121; RP=0.733), and ACH (p=0.791; RP=1.088) with SBS. In conclusion, this study identified no relationship between indoor air quality and the incidence of SBS among employees of the Central Java Provincial Archives and Library Office. Keywords: Indoor Air Quality, Sick Building Syndrome, Risk Factors, Workers.